2022
DOI: 10.1108/caer-01-2022-0003
|View full text |Cite
|
Sign up to set email alerts
|

Food price dynamics and regional clusters: machine learning analysis of egg prices in China

Abstract: PurposeThe study uses machine learning techniques to cluster regional retail egg prices after 2000 in China. Furthermore, it combines machine learning results with econometric models to study determinants of cluster affiliation. Eggs are an inexpensiv, nutritious and sustainable animal food. Contextually, China is the largest country in the world in terms of both egg production and consumption. Regional clustering can help governments to imporve the precision of price policies and help producers make better in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
(90 reference statements)
0
6
0
Order By: Relevance
“…Liu et al . (2023) used the dynamic time warping (DTW) method to cluster time-series data of egg prices across provinces in China and identified three different clusters.…”
Section: Machine Learning and Its Application In Agricultural Economicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Liu et al . (2023) used the dynamic time warping (DTW) method to cluster time-series data of egg prices across provinces in China and identified three different clusters.…”
Section: Machine Learning and Its Application In Agricultural Economicsmentioning
confidence: 99%
“…For instance, Graskemper et al (2021) used a clustering algorithm and found three types of farms in Germany, and suggested different policies that should be made toward each group. In this special section, two papers (Zeng and Chen, 2023;Liu et al, 2023) used different clustering algorithms to study two important policy issues: rural-urban integration and egg price clustering at the provincial level of China. Given the sheer size of China and the heterogeneous development levels between regions, such studies could help make more precise policies in these fields.…”
Section: Clusteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining investments and innovations into one system will lead to the successful development of the level of economic recovery. One of the new directions of agricultural formations is agricultural clusters [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Reference [2] made a chicken egg incubator connected to the Internet of things (IoT) and supplied solar energy. In machine learning, [3] predicted the price of chicken eggs using dynamic time warping (DTW) to make investing easier for chicken egg businesspeople. Reference [4] used a support vector machine (SVM) to predict the category of chicken eggs based on a combination of images and sensor metrics.…”
Section: Introductionmentioning
confidence: 99%